Improving of Nutraceutical Features of Many Important Mediterranean Vegetables by Inoculation with a New Commercial Product - Raiola, Assunta; C. Tenore, Gian; Petito, Raffaele; Ciampaglia, Roberto; Ritieni, Alberto (Current Pharmaceutical Biotechnology, 2015)
Several epidemiological studies show that fruits, vegetables and cereals can play a nutraceutical role for their content of many antioxidant phytochemicals such as carotenoids, ascorbic acid and phenolics. A commercial inoculant (MICOSAT F®) containing arbuscular mycorrhizal fungi (AMF) could improve the nutritional value in crops. The goal of this work was to evaluate the effect of AMF on the production level of carotenoids, AsA, phenols including antocyanins and saponins, proteins, total antioxidant activity and nitrates in fruits, vegetables, legumes and durum wheat var. grecale, whose consumption is largely recommended according to Mediterranean diet. The treatment increased the antioxidant activity in strawberries (37.50%), in giant lentils (29.17%) and in durum wheat (63.63%) but decreased it in kiwi (31.81%) and in grape (19.81%). Nitrate levels decreased significantly in strawberries (39.78%) and in tomato intended for transformation (37.79%). The application of MICOSAT F® enhanced the levels of several secondary metabolites. However, the amount of phytochemicals and respective by-products were reduced in some cases. Environmental conditions and modality of AMF inoculation could module both primary and secondary metabolites.
Keywords: Arbuscular Mycorrhizal Fungi